Комплементарний підхід до вивчення розвитку національної економіки - Разумова, Г.В. (Економічний вісник Донбасу, 2019)
Визначено основну класифікаційну ознаку, яка є першочерговою по відношенню до поняття розвитку з точки зору методології побудови його оцінки, – агрегованість. Виокремлено такі критерії типології розвитку, як: характер змін, еластичність до впливу та складність об’єкту.
Запропоновано комплементарний підхід до вивчення розвитку національної економіки, який передбачає органічне поєднання окремих елементів класифікації та типології розвитку, що дозволяє розглядати розвиток національної економіки з декомпонуванням за її найважливішими сферами, розподіляти їх відповідно прискорення чи вповільнення, а також дає змогу встановити, наскільки розвиток в окремій сфері національної економіки є еластичним до впливу до регулювання. Определен основной классификационный признак, который является первоочередным по отношению к понятию развития с точки зрения методологии построения его оценки, – агрегированность. Выделены такие критерии типологии развития: характер изменений, эластичность к влиянию и сложность объекта.
Предложен комплементарный подход к изучению развития национальной экономики, который предполагает органическое сочетание отдельных элементов классификации и типологии развития, позволяет рассматривать развитие национальной экономики с декомпонированием по ее важнейшим сферам, распределять их в соответствии ускорения или замедления, а также позволяет установить, насколько развитие в отдельной сфере национальной экономики является эластичным к воздействию регулирования. The national economy is a complex and multi-aspect system, so its development should be scrutinized as the development of economic system. The complexity of economic systems and the transience of economic processes require constant study, analysis, revision and expansion of theoretical approaches and concepts, as well as studying laws of development. The article is devoted to the substantiation of theoretical issues concerning the development of national economy and its types.
The purpose of the article is to develop a complementary approach, involving the development study based on the method of typology and the method of classification supplementary.
The basic scientific approaches, dictionary materials and other sources of information on the definition of development, its types and combinations are analyzed.
During the study, such main classification characteristic as aggregation is determined. It is a priority feature to the notion of development from the view of evaluation scheme methodology. The given classification characteristic includes the division of the types of development based on the aggregate evaluation; according to this division certain types of development can be defined, such as particular field, regional, particular industry and national economy.
These are the criteria of the typology of development, as the character of changes (development in the form of acceleration or deceleration of changes in key indicators), flexibility to influence (flexible and non-flexible development to regulatory influence) and the complexity of object (total and partial development). At the same time, a simultaneous application of the typology criteria and classification characteristics is advisable, which is possible on the basis of a complementary approach.
During the research, complementarity is used for describing and structuring the development of a combination of its types into separate class, which collectively will give the most complete qualitative characteristics. As a result of the research, we obtain information not about abstract properties of the development, but about specific properties of the development of national economy in the spheres according to its research structuring.
The complementary approach to the study of the development of a national economy is proposed. The approach provides for the integrated combination of separate elements of classification and development typology, which allows considering the development of a national economy with a differentiation into the most important fields, to divide them according to growth or regression; and it also allows clarifying how much development in a particular field of national economy is flexible to the influence of regulation.